Arterial blood supply of ovaries: a comprehensive review - Monika Konarska-Włosińska; Ameen Nasser; Patryk Ostrowski; Michał Bonczar; Kajetan Ochwat; Jerzy A. Walocha; Mateusz Koziej (Folia Morphologica)
The ovaries, resembling almonds both in shape and size, are vital organs that serve as the female gonads where oocytes, or female gametes, undergo development and where various reproductive hormones are produced. The ovaries receive their arterial blood supply predominately from the ovarian artery, but also from the ascending branches of the uterine artery. The arterial anatomy of the ovaries is highly significant in any gynaecological surgical procedure, as haemorrhagic complications can be fatal. Therefore, the main objective of the present review was to comprehensively describe the complete anatomy of the arterial blood supply of the ovaries. The arterial blood supply to the ovaries is facilitated by a complex network of arteries, frequently characterised by diverse anastomoses. Notably, the ovarian artery and uterine artery exhibit significant variability, presenting challenges for physicians performing gynaecological and endovascular procedures. This study showcases comprehensive and detailed insights into the arterial blood supply of the ovaries, serving as a valuable resource for practitioners navigating the complexities of these procedures. By offering clear and detailed information, the present study aimed to enhance the effectiveness and safety of medical interventions involving the ovaries.